Efektivitas Ramuan Asam Jawa (Tamarindus Indica L.) Dan Garam Pada Ibu Menyusui Dengan Bendungan ASI Di Puskesmas Mumbulsari - erlin chusnia putri (Jurnal Keperawatan Terapan, 2018)
Breast Engorgement was damming milk due to narrowing ductus lactiferous or by glands not emptied perfect. The mechanism of Engorgement is vasoconstriction caused by prostaglandins. Strategies to reduce the engorgement by using Asam Jawa and salt. When the intervention is bad then engorgement can disrupt milk production and inhibit breastfeeding. The purpose of this research is to analyze the effectiveness of Asam Jawa and salt to engorgement of breastfeeding mother at Mumbulsari Community Health Center. The research design Quasi-experiment, Pre and post-test one group design. Sample: 15 breastfeeding mothers with breast engorgement. The research instrument used observation sheet to assess the level of the Engorgement. Resulth Wilcoxon test obtained p value is 0.000, which means an Asam Jawa and salt effective for breast engorgement in breastfeeding mothers. Based on the result of the research above, in Asam Jawa and salt contains essential oil, flavonoid, tanin and natrium clorida, all of them can prevent biosynthesis of prostaglandin so it could reduce swelling and pain, antibacterials, and natrium can reduce edema. Asam Jawa and salt effective to resolve breast engorgement.